Influence of Mixing Time to Crystal Structure and Dielectric Constant of Ba0,9Sr0,1TiO3 - Dianisa Khoirum Sandi; Agus Supriyanto; Anif Jamaludin; Yofentina Iriani (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2015)
Barium Strontium Titanate (Ba1-xSrxTiO3) or BST has been synthesized using solid state reaction method. Raw materials of BST were BaCO3, SrCO3, and TiO2. Those materials were mixed, pressed, and sintered at temperature 1200oC for 2 h. Mixing time of raw materials was varied to identify its effects on crystal structures and dielectrics constant of Ba0.9Sr0.1TiO3 using X-Ray Diffraction (XRD) and LCR meter instrument, respectively. The results of XRD showed that crystals structure of Ba0.9Sr0.1TiO3 is tetragonal. Lattice parameter of Ba0.9Sr0.1TiO3 for 6 h of mixing time is a = b = 3.988 Å and c = 3.998 Å. Lattice parameter of Ba0.9Sr0.1TiO3 for 8 h of mixing time is a = b = 3.976 Å and c = 4.000 Å. Crystalline size of Ba0.9Sr0.1TiO3 was calculated using Scherrer equation. Crystalline size, crystallinity, and dielectric constant of Ba0.9Sr0.1TiO3 for 6 h of mixing time is 38 nm, 96%, and 115 at frequency 1 KHz, respectively while their value for 8 h of mixing time is 39 nm, 96%, and 196 at frequency 1 KHz, respectively. Thus it can be concluded that mixing time affects the lattice parameters of Ba0.9Sr0.1TiO3 crystal. The longer mixing time causes crystalline size, crystallinity, and dielectrics constant increase.